Development and verification of an integrated hydration, geochemical and transport model for the hydrated cement paste exposed to an aggressive chemical environment - Krishnya, S.; Kopitha, K.; Yoda, Y.; Kitagaki, R.; Elakneswaran, Y. (Elsevier, 2023)
This study established a new transport model by using the COMSOL-IPHREEQC interface to simulate the changes in the morphology of hydrated cement paste due to the diffusion of carbon dioxide and chloride ion. A series of constitutive models such as the cement hydration model (to compute the dissolution rate of each clinker mineral), thermodynamic model (to perform the hydration reaction, reaction due to transport of ions, chemical and physical adsorption of chloride ion during the chloride ion ingression and dissolution rate of calcium-silica- hydrate (C–S–H) simultaneously with portlandite for the carbonation), porosity determination, and COMSOL Multiphysics (for the calculation of transport problems) were integrated using MATLAB language to determine the pore solution chemistry, hydrates assemblage, and porosity of the cement paste exposed to aggressive environments. During the diffusion of carbon dioxide gas, the decalcification of C–S–H was realistically considered by assuming that the Ca/Si ratio of C–S–H decreased from 1.67 (Jennite type C–S–H) to 0.67 (Tobermorite C–S–H), and then from 0.67 to 0 (silica gel). The proposed integrated platform was well verified with different sets of reported and raw experimental results and existing models, indicating a realistic predictability for chloride ion ingression and carbonation. The developed model discloses the effect of coupling the progression of hydration with reaction due to the transport of ions by using the free chloride ion profile and phase assemblages during the chloride ion ingression.
Keywords: COMSOL-IPHREEQC; Carbonation; Chloride ion diffusion; Hydration products; Porosity; Cement paste